Pengaruh Kebijakan Harga terhadap Minat Mahasiswa Perguruan Tinggi di Kota Pagar Alam (Studi Kasus Pada 5 Perguruan Tinggi di Kota Pagar Alam STIT Pagar Alam ITBis Lembah Dempo, STKIP Muhammadiyah Pagar Alam, STEBIS Pagar Alam, Sekolah Tinggi Teknologi Pa - Sastra Mico (UNIVED Press, 2022)
This study aims to determine the effect of price policy on the interest of college students in Pagar Alam City. The method used in sampling is proposive sampling. The sample in this study amounted to 50 people who were taken randomly from 5 universities in the city of Pagar Alam. The collection is done by using a questionnaire method that has been tested for validity and reliability. Based on the results of the t test on the price policy variable, it was obtained at 2,949, while in this study it was 2,949, so it can be said > , and it can be concluded that in the t test in this study